The Role of Mitophagy in Innate Immunity - Gkikas, Ilias; Palikaras, Konstantinos; Tavernarakis, Nektarios (Frontiers in Immunology, 2018)
Mitochondria are cellular organelles essential for multiple biological processes, including energy production, metabolites biosynthesis, cell death and immunological responses among others. Recent advances in the field of immunology research reveal the pivotal role of energy metabolism in innate immune cells fate and function. Therefore, the maintenance of mitochondrial network integrity and activity is a prerequisite for immune system homeostasis. Mitochondrial selective autophagy, known as mitophagy, surveils mitochondrial population eliminating superfluous and/or impaired organelles and mediating cellular survival and viability in response to injury/trauma and infection. Defective removal of damaged mitochondria leads to hyperactivation of inflammatory signaling pathways and subsequently to chronic systemic inflammation and development of inflammatory diseases. Here, we review the molecular mechanisms of mitophagy and highlight its critical role in the innate immune system homeostasis.